KOREAN LANGUAGE EDUCATION IN THE ERA OF GLOBALIZATION - WITH THE FOCUS ON BOOKS AND TEACHING MATERIALS - - BOROWIAK, Anna; LIM, Choonsil (International Journal of Korean Humanities and Social Sciences, 2019)
A keen interest in the culture and economic development of the Republic of Korea has resulted in establishing business relations between Korea and various countries all around the world. The Korean War (1950-1953) is said to be the catalyst for Korean Studies, since it has generated a considerable interest in Korean history, language and culture. Yet, when the Korean Language Education (henceforward KLE) is being referred to, usually the years when the boom for "everything that is Korean” started, which could be attributed to the successfully organized Summer Olympics in 1988 and co-organized Asian World Cup in 2002, are being mentioned. This was when the world saw a different side of Korea. However, also thanks to the enormous popularity of Hallyu and the support of the South Korean Government given to initiatives, which among others, popularize the Korean language, the interest in various aspects of Korean culture as well as the language itself, has become higher than ever before. Since the turn of the 21st century, South Korea is perceived as one of the world's leading exporters of culture and tourism, and Hangeul became one of the exported goods. The aim of this research is to analyze the situation of KLE in the era of globalization, which along with the spread of lingua franca, among them English, is endangering the language variety of the world. In order to do so, several significant dates and initiatives showing how Korean scholars and the Government have influenced and shaped the language policy and thus have contributed to the popularization of the language all around the world will also be referred to. Government sponsored institutions providing Korean language classes, as well as books and other teaching materials, will be discussed and classified. The article will also try to answer the question concerning the future of the KLE.